Web-based system for prioritization of research area in FSKM: a web system engineering approach / Mohd Azmeer Omar - Omar, Mohd Azmeer (2012)
Faculty of Computer & Mathematical Sciences (FSKM) UiTM has been established since 1966. The school offers various programmes such as computer science, networking, multimedia, intelligent system and many more for student to choose, from Diploma up PhD level. Until now, there is no system to identify the most important research areas for student to take when doing a thesis or IT project. With the absence of a reference on important research areas, students and lecturers may not only lose focus, but also repeat similar research or even worse do exactly the same research. Focusing on specific research areas that is desired for current market will not only can bring greater value to the university but also to the students, which can help them to start career after graduated. Therefore, lecturer and supervisor must play important role to decide which research area is important. To solve this problem, researcher developed a new system to help lecturer to prioritize the most important research area. The system that has been developed is capable to allow lecturer to rate each research areas using star rating system. Then the most important research is calculated using scoring algorithm. The systems is developed using web system engineering approach with the latest Java technology and web framework to simplify development process. As a result, lecturer can use the analytical chart and listing report generated by system to help them to make decision-making on the direction of research areas.